2015
DOI: 10.1590/s2179-975x1115
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrates of the Iranian running waters: a review

Abstract: A comprehensive review of macroinvertebrate studies conducted along the Iranian running waters over the last 15 years has been made by providing the most updated checklist of the Iranian running waters benthic invertebrates. Running waters ecosystems are complex environments known for their importance in terms of biodiversity. As part of the analysis, we endeavored to provide the critical re-identification of the reported species by through comparisons with the database of the Animal Diversity Web (ADW) and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
(17 reference statements)
0
11
0
1
Order By: Relevance
“…The evaluation of ecosystem pollution and the assessment of biota responses to environmental changes have received increasing attention from scientists (Azrina et al, 2006;Chen et al, 2013;Taherizadeh and Sharifinia, 2015;Mangadze et al, 2016). Biological monitoring programs are widely applied in developed countries and suggest many advantages in assessing ecological outcomes of perturbations in developing countries (Sharifinia, 2015). Currently, many indices based on macroinvertebrate communities are used as effective tools for assessment of health or pollution status in freshwater ecosystems, because they are comparatively easy and affordable to collect (Mangadze et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of ecosystem pollution and the assessment of biota responses to environmental changes have received increasing attention from scientists (Azrina et al, 2006;Chen et al, 2013;Taherizadeh and Sharifinia, 2015;Mangadze et al, 2016). Biological monitoring programs are widely applied in developed countries and suggest many advantages in assessing ecological outcomes of perturbations in developing countries (Sharifinia, 2015). Currently, many indices based on macroinvertebrate communities are used as effective tools for assessment of health or pollution status in freshwater ecosystems, because they are comparatively easy and affordable to collect (Mangadze et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the Nearctic/Neotropic genus Callibaetis could refer to cosmopolitan Cloeon , and the Nearctic/Neotropic genus Tricorythodes seems to refer to cosmopolitan Caenis , etc. A review of macroinvertebrates of Iranian running waters by Sharifinia (2015), despite promising “critical re-identification of the reported species”, includes such confusing data not only in mayflies, but also in Plecoptera. Therefore, we do not recommend using this list as reliable and valid source of information on the diversity of Iranian benthic insects.…”
Section: Affinities Of Procloeon (Pseudocentroptilum) Caspicum Sp Nmentioning
confidence: 99%
“…A detailed review of literature revealed 42 references published in international journals accessible to the scientific public. Publications written in Persian (Farsi) were previously reviewed by Sharifinia (2015) and they did not include any species not reported in international sources reviewed (cf. Table 2 summarizing macroinvertebrate diversity in Sharifinia 2015).…”
Section: Affinities Of Procloeon (Pseudocentroptilum) Caspicum Sp Nmentioning
confidence: 99%
See 2 more Smart Citations